Implementasi IVA Test Sebagai Penapisan Kanker Mulut Rahim Di Kelurahan Kwala Bekala - Riska Susanti Pasaribu; Ingka Kristina Pangaribuan; Lidya Natalia Sinuhaji; Lisa Putri Utami Damanik; Ninsah Mandala Putri Sembiring; Ika Damayanti Sipayung (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The number of cervical cancer sufferers in Indonesia is getting higher. Health promotion and early detection are priorities for preventing and treating disease. Cervical cancer is the most common cancer. The purpose of the IVA examination is to reduce the morbidity of the disease by early treatment of cases found to determine abnormalities in the cervix. The target of implementing community service is women of childbearing age who have been active in conjugal relations in the kwala bekala village, Medan city with 135 participants. The research method used is quantitative method with simple random sampling technique by conducting direct interviews and unplanned questions. The results of this study indicate that counseling and early detection of cervical cancer with the IVA test were carried out where the participants totaled 135 people, it was stated that 4 people had positive test results that had cancerous lesions and the results of these tests had been reported to the puskesmas.